A secure audio steganography approach - Zamani, Mazdak; Abdul Manaf, Azizah; Ahmad, Rabiah; Jaryani, Farhang; Taherdoost, Hamed; Zeki, Akram M. (Institute of Electrical and Electronics Engineers ( IEEE ), 2009)
A wide range of steganography techniques has been described in this paper. Beside the evaluation of embedding parameters for the existing techniques, two problems -weaknesses- of substitution techniques are investigated which if they could be solved, the large capacity - strength- of substitution techniques would be practical. Furthermore, a novel, principled approach to resolve the problems is presented. Using the proposed genetic algorithm, message bits are embedded into multiple, vague and higher LSB layers, resulting in increased robustness.